Sistem Informasi Manajemen Pos Pelayanan TerpaduKesehatan Jiwa di Desa Bongkot - Athi Linda Yani; Mohamad Ali Murtadho (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
Bongkot village has many people suffering from mental disorders. There are around fifty people suffering from mental disorders. Prediction of mental disorders at table three is usually done through interviews. Cadres need to fill out the form provided on the Towards Healthy Soul Card (KMSJ) at the interview. The form needs to be filled out based on the results of the interview to predict whether the interviewee has a mental illness or not. If the results of the interview are predicted to have a mental disorder, the cadre will recommend appropriate follow-up. This process is certainly prone to mistakes because it only depends on cadre knowledge. Predictions will certainly affect the recommendations given. in this community service program, the authors propose to apply Information Technology (IT) to reduce the risk of such errors. The system is named the Mental Health Posyandu Management Information System (SIM). The system is expected to be able to improve the efficiency and effectiveness of services at the posyandu, the output of this service produces an online-based application related to the service of mental health posyandu with the address www. poskeswa.com.